EVALUATION OF IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEMS AND INTERNAL CONTROL SYSTEMS IN FINISHED GOODS INVENTORY AT PT ISKANDAR INDAH PRINTING TEXTILE SURAKARTA - Totok Mardianto (Universitas Maarif Hasyim Latif, 2023)
This research was conducted at companies engaged in the textile sector. The purpose of this research is to find out how the accounting information system and internal control system are applied to the finished goods inventory at PT Iskandar Indah Printing Textile and to find out how the accounting information system and internal control system for finished goods inventory at PT Iskandar Indah Printing Textile are by the theory stated. There is. The method used in this research is qualitative. Data collection techniques used are interviews, observation and documentation. The data analysis technique used in this study is by (1) Collecting data to get the desired information. (2) Reducing data or summarizing the main things. (3) Presenting data to conclude. (4) Summarize the research results.The results showed that the finished goods inventory accounting information system implemented at PT Iskandar Indah Printing Textile indicated that the tasks or functions carried out and the recording and reporting system regarding dead goods inventory management activities had been practical. Meanwhile, the internal control system for finished goods inventory still has a dual function/task of the warehouse department. Based on the practice that occurred at PT Iskandar Indah Printing Textile, by looking at the existing theory, the situation is still not by the idea. Still, the company can adequately run the accounting information and internal control systems on finished goods inventory.